2010
DOI: 10.1159/000273468
|View full text |Cite
|
Sign up to set email alerts
|

Early and Late Graft Function after Laparoscopic Hand-Assisted Donor Nephrectomy for Living Kidney Transplantation: Comparison with Open Donor Nephrectomy

Abstract: Background and Purpose: Laparoscopic donor nephrectomy has become the procedure of choice for living kidney transplantation in many centers. We report on our experience with laparoscopic hand-assisted donor nephrectomy, in particular concerning graft function compared with open donor nephrectomy. Materials and Methods: Between 1995 and March 2007, 72 patients with end-stage renal disease have received kidney transplantation from living donors. Open living donor nephrectomy (ODN) was performed in 35 donors, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
2
3
0
Order By: Relevance
“…54,55 More recent publications show that overall complication rates of LDN range from 4 to 30%, 44,56 which is in line with the complication rates we found. One could argue that the included studies in our analysis are hard to compare because not all of them assessed the same type of complications.…”
Section: Discussionsupporting
confidence: 90%
“…54,55 More recent publications show that overall complication rates of LDN range from 4 to 30%, 44,56 which is in line with the complication rates we found. One could argue that the included studies in our analysis are hard to compare because not all of them assessed the same type of complications.…”
Section: Discussionsupporting
confidence: 90%
“…The findings of improved early function and reduced resistive indices are similar to those shown in studies of expanded criteria and DCDD kidneys when HMP was compared to SCS. The average serum creatinine at 1 year in our SCS group (135 AE 48.7 lmol/l) and our HMP group (111 AE 29 lmol/l, P = 0.03 vs. SCS group) is in keeping with and seems slightly lower, respectively, compared to values reported in other studies of LDK [21][22][23]. In one study [21], comparing laparoscopic to open donor nephrectomy, the mean creatinine at 1 year in the laparoscopic group was 130 AE 46 lmol/l.…”
Section: Discussionsupporting
confidence: 87%
“…In one study , comparing laparoscopic to open donor nephrectomy, the mean creatinine at 1 year in the laparoscopic group was 130 ± 46 μmol/l. In another study , comparing different approaches to living donor nephrectomy, the one‐year creatinine was 132 ± 56 μmol/l.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Living donor nephrectomy was first introduced 50 years ago. 3 Since then, numerous studies have shown superior outcomes over deceased donor nephrectomy with regards to long-term patient and graft survival. 4 A number of surgical techniques have been developed to minimize morbidity for donors, while maintaining optimal function of transplanted kidneys for recipients.…”
Section: Introductionmentioning
confidence: 99%